Efeitos sistemáticos na análise de sobrevivência de codornas de corte - Almeida, Bárbara Helena Mota de (2020)
Quail is an avian species of late domestication when compared to the chicken, such fact results in less adaptation to intensive rearing systems. Mortality is among the major factors in the quail industry, not only for moral and ethical reasons but also for economic impacts. The aim of this study was to analyze effects that influence meat quail mortality. We analyzed the following factors: hatch weight (less or greater than 10g), weight loss (present or absent), hatching (three different hatchings), gender (male or female) and production system (cage or floor). Firstly, assumptions of Cox model were checked, restricting periods of no records of gender (male or female) production system (cage or floor). First, assumptions of Cox model were checked, also restricting periods where effects where gender and production system were not recorded. We stablished four time periods to analyze, up to 28 days, from 28 to 42 days, 42 to 77 days, and 77 to 150 days of age. The effect of bodyweight loss had the most significant at all periods in this analysis and could be linked to occurrence of diseases and feed restriction for these animals. Besides of significant only at the first period of life, hath weight must be monitored for its influence on the highest proportion on mortality in this study. Effects of hatching, and gender had association with mortality only in specific periods and could be related to specific environmental conditions affecting these effects. Production system effect had high variability on its estimates of risk, thus no effect was detected.